2015
DOI: 10.1111/mmi.13056
|View full text |Cite
|
Sign up to set email alerts
|

Interactive regulation by the Bacillus subtilis global regulators CodY and ScoC

Abstract: SUMMARY CodY and ScoC are Bacillus subtilis transcriptional regulators that control the expression of dozens of genes and operons. Using scoC-lacZ fusions and DNA-binding experiments, we show here that scoC is directly repressed by CodY. This effect creates multiple forms of cascade regulation. For instance, expression of the dtpT gene, which is directly and negatively controlled by ScoC and encodes a putative oligopeptide permease, was activated indirectly by CodY due to CodY-mediated repression of scoC. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 82 publications
2
40
0
Order By: Relevance
“…We concluded that both CodY and ScoC are strong repressors of the aprE gene and that each is sufficient for efficient repression in the absence of the other. Moreover, given that the difference in aprE expression between the codY ϩ scoC ϩ strain, BB3912, and the codY scoC double mutant strain, BB3910, was only 32-fold (Table 3), the effects of CodY and ScoC on aprE are not multiplicative, in accord with the previous observation that the two proteins do not act completely independently of each other due to scoC repression by CodY (41).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…We concluded that both CodY and ScoC are strong repressors of the aprE gene and that each is sufficient for efficient repression in the absence of the other. Moreover, given that the difference in aprE expression between the codY ϩ scoC ϩ strain, BB3912, and the codY scoC double mutant strain, BB3910, was only 32-fold (Table 3), the effects of CodY and ScoC on aprE are not multiplicative, in accord with the previous observation that the two proteins do not act completely independently of each other due to scoC repression by CodY (41).…”
Section: Resultssupporting
confidence: 71%
“…The procedures for gel shift and DNase I footprinting experiments were as described previously (41). Samples contained various amounts of proteins, a vast excess of unlabeled salmon sperm DNA, and Յ0.1 or 2 to 4 nM labeled DNA for gel shift or DNase I footprinting experiments, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ScoC directly downregulates opp, app, and sinIR expression (87,88), suggesting that ScoC may inhibit sporulation under high-nutrient conditions by repressing the expression of genes involved in early sporulation events. Further, CodY directly represses scoC transcription, and CodY and ScoC independently coregulate several loci, including opp (89,90). Altogether, these results imply that multiple regulators control B. subtilis sporulation through nutrient-dependent alteration of early sporulation gene expression.…”
Section: Discussionmentioning
confidence: 55%